Arrhythmia induced cardiomyopathy. Issue 4 (20th July 2018) - Sugumar, Hariharan; Prabhu, Sandeep; Voskoboinik, Aleksandr; Kistler, Peter M.
Abstract: Arrhythmia induced cardiomyopathies (AIC) refer to the collective condition of Arrhythmia, Tachycardia, and ectopy‐induced Cardiomyopathy. Atrial fibrillation (AF) and heart failure (HF) are modern epidemics that often coexist and exacerbate one another. We aim to provide an overview of the current understanding and evidence for treatment and management in AIC with a particular focus on AF‐mediated cardiomyopathy and suggest approaches to recognize, screen, and manage AIC.